Cystic Fibrosis Cloud database: Un sistema informático para el almacenamiento y manejo de datos clínicos y microbiológicos del paciente con fibrosis quística - Prieto, Claudia Inés (2016)
The epidemiological and clinical management of cystic fibrosis (CF) patients suf-fering from acute pulmonary exacerbations or chronic lung infections demands continuousupdating of medical and microbiological processes associated with the constant evolution ofpathogens during host colonization. In order to monitor the dynamics of these processes, it isessential to have expert systems capable of storing and subsequently extracting the informa-tion generated from different studies of the patients and microorganisms isolated from them.In this work we have designed and developed an on-line database based on an informationsystem that allows to store, manage and visualize data from clinical studies and microbiological analysis of bacteria obtained from the respiratory tract of patients suffering from cysticfibrosis. The information system, named Cystic Fibrosis Cloud database is available on the http://servoy.infocomsa.com/cfcdatabasesite and is composed of a main database and a web-based interface, which uses Servoy's product architecture based on Java technology. Althoughthe CFC database system can be implemented as a local program for private use in CF centers,it can also be used, updated and shared by different users who can access the stored infor-mation in a systematic, practical and safe manner. The implementation of the CFC databasecould have a significant impact on the monitoring of respiratory infections, the prevention ofexacerbations, the detection of emerging organisms, and the adequacy of control strategies forlung infections in CF patients.